The Impact of Cloud Technology and Integration Solutions on Public Sector Regulatory Systems - Nethaji Kapavarapu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of cloud technology and advanced digital solutions has revolutionized public sector regulatory systems, transforming traditional paper-based processes into efficient, automated operations. This transformation encompasses comprehensive frameworks for compliance monitoring, enforcement mechanisms, and public service delivery. The implementation of sophisticated API architectures and real-time monitoring capabilities has enhanced system interconnectivity while ensuring robust security protocols. The adoption of cloud-based platforms has significantly improved citizen engagement through intuitive interfaces and streamlined application processes. Integration challenges, including data sovereignty and legacy system compatibility, have been addressed through structured migration strategies and enhanced security frameworks. Looking ahead, emerging technologies such as artificial intelligence, machine learning, and Internet of Things are shaping the future of regulatory management, enabling predictive compliance monitoring and automated enforcement actions while maintaining transparency and accountability in public sector operations.
Keywords: Cloud Integration; Regulatory Compliance; Digital Transformation; Service Automation; Predictive Analytics